2006
DOI: 10.1128/iai.74.2.953-960.2006
|View full text |Cite
|
Sign up to set email alerts
|

The ProtozoanNeospora caninumDirectly Triggers Bovine NK Cells To Produce Gamma Interferon and To Kill Infected Fibroblasts

Abstract: Natural killer (NK) cells are considered to be key players in the early innate responses to protozoan infections, primarily indirectly by producing gamma interferon (IFN-␥) in response to cytokines, like interleukin 12 (IL-12). We demonstrate that live, as well as heat-inactivated, tachyzoites of Neospora caninum, a Toxoplasma-like protozoan, directly trigger production of IFN-␥ from purified, IL-2-activated bovine NK cells. This response occurred independently of IL-12 but was increased by the addition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 48 publications
2
37
0
1
Order By: Relevance
“…It has also been reported that the infective forms of Leishmania species (live promastigotes) are able to directly activate NK cells to secrete IFN-␥ in the absence of accessory cells (7,24). Finally, evidence for a direct contact between bovine NK cells and the protozoan Neospora caninum has recently been reported (9).…”
mentioning
confidence: 96%
“…It has also been reported that the infective forms of Leishmania species (live promastigotes) are able to directly activate NK cells to secrete IFN-␥ in the absence of accessory cells (7,24). Finally, evidence for a direct contact between bovine NK cells and the protozoan Neospora caninum has recently been reported (9).…”
mentioning
confidence: 96%
“…A former study indicated that N. caninum directly become a trigger for the production of IFN- from purified, IL-2-activated bovine NK cells which killed infected fibroblasts [5]. Furthermore, NK cells have been shown to act as early responders in experimental infection with N. caninum in calves [19].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, innate cells, such as natural killer (NK) cells and NKT cells, play essential roles as primary effector cells at the interface between the host and parasite until the establishment of adaptive immunity [16]. Previously, it has been shown that N. caninum becomes a trigger to produce IFN- in bovine NK cells [5,19]. However, the role of NK or NKT cells in the defense against N. caninum has not been well clarified.…”
mentioning
confidence: 99%
“…For example, Pfefferkorn found that the IFN-␥-inducible tryptophan-degrading enzyme IDO is capable of blocking the growth of T. gondii (36). Proliferation of N. caninum in bovine fibroblasts was analyzed in a coculture system consisting of N. caninum-infected fibroblasts and bovine NK cells (6). Boysen et al found that N. caninuminfected fibroblasts induce IFN-␥ production in NK cells, which inhibit N. caninum growth by killing infected fibroblasts.…”
Section: Discussionmentioning
confidence: 99%